(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The purpose of this study is to know (1) Promotion of positions held; (2) Employee job satisfaction; (3) employee performance; (4 The influence of promotion and job satisfaction on employee performance in Banking in Banten, either simultaneously or partially The method used is descriptive survey method and explanatory. The unit of analysis in this research is the employees of Banking in Banten, with a sample of 50 people, and the method of analysis used is the frequency distribution and path analysis. Based on the results of the analysis, then obtained as follows, Promotion positionsBanking in Banten has in accordance with the field and expertise, Job Satisfaction employees of Banking in Banten currently considered satisfied, Employees of Banking in Banten is considered to have a high enough performance as well as job promotion and job satisfaction affect the performance of employees of Banking in Banten, but when viewed partially, it turns out the promotion of dominant positions affects their performance